The Influence of Work-Life Balance and Perceived Organizational Support on Employee Well-Being: The Mediating Role of Employee Job Satisfaction at PT. Pelabuhan Indonesia (Persero) Bengkulu Branch - Suradi, Pujud; Nasution (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of work-life balance and perceived organizational support on employee well-being, with job satisfaction as a mediator, at PT Pelabuhan Indonesia (Persero) Bengkulu Branch. Using a quantitative survey of 100 employees, data were analyzed via PLS-SEM with SmartPLS 4.0. Results show that work-life balance positively affects job satisfaction, which in turn enhances well-being. Perceived organizational support directly improves well-being but does not affect job satisfaction. Job satisfaction mediates the effect of work-life balance on well-being but not that of organizational support. Findings highlight the importance of organizational support and job satisfaction in promoting well-being.